(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In this article the exogenous variables in the model pageween the value of regressiya korrelyativ multikollinearlikni and quotes. Common delays in the context of distributed delay are connected mutually of the variables when the response is difficult and individual evaluation of the importance of the individual parameters on the valuation koeffisiyentlar indicated. The alm method upon a distributed lag model is a “how to” settling the presence ofkthrough the installation of a certain structure in the distribution echikish a free estimate to solve the problems of the specific multikollinearlik, alm, offer a draw the structure of my function with the method of polina delay, that is, given a few years after the appearance of its results. Alm, on the method of distributed lag model was composed of. Figure the distribution of emergency situations models are listed. Modern mathematical methods and modeling of emergency situations with the speed of options here ommaboplik be explained by expanding the use of information technology influencessaid. A model in the framework of statistical and mathematical methods, variasion and dispersion analysis, and regression analysis korrelyativ the associated equations, statistical, statistical indices, final, updated and expanded, and other equations are integrated, and which matrisa analysis, mathematical programming methods, processes, research, public service systems, systems modeling and analysis, and an intuitive empirical methods was shown.